2019
DOI: 10.1039/c9cc03791h
|View full text |Cite
|
Sign up to set email alerts
|

Covalently bound monolayer patterns obtained by plasma etching on glass surfaces

Abstract: Plasma etching: a reproducible, simple and fast method for creating unconventional sub-10 μm patterns without the need of a clean room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…They range from the preparation of glassware prior to anionic polymerizations with tBuLi, crystallizations, the uniform deposition of silane monolayers on glass for biosensing systems (for which traces of water are required), [17] the critical role of water under hydrophobic confinement in nanotechnology and nanoscience, [18] water traces in chemical vapor deposition in terms of their reproducibilty, coverage, and material quality, [19] to lithography on glass surfaces. [20] Furthermore, the interaction of biomaterials with biomaterial surfaces is significantly influenced by water, which is the first contact before ions and proteins are adsorbed and finally the surrounding cells approach the material, [21] making its detection on the underlying glass surfaces highly desirable. The interaction between glass and atmospheric water is the beginning of the deterioration of glass, e. g. 16th and 17th century Venetian glassware, which must be protected.…”
Section: Resultsmentioning
confidence: 99%
“…They range from the preparation of glassware prior to anionic polymerizations with tBuLi, crystallizations, the uniform deposition of silane monolayers on glass for biosensing systems (for which traces of water are required), [17] the critical role of water under hydrophobic confinement in nanotechnology and nanoscience, [18] water traces in chemical vapor deposition in terms of their reproducibilty, coverage, and material quality, [19] to lithography on glass surfaces. [20] Furthermore, the interaction of biomaterials with biomaterial surfaces is significantly influenced by water, which is the first contact before ions and proteins are adsorbed and finally the surrounding cells approach the material, [21] making its detection on the underlying glass surfaces highly desirable. The interaction between glass and atmospheric water is the beginning of the deterioration of glass, e. g. 16th and 17th century Venetian glassware, which must be protected.…”
Section: Resultsmentioning
confidence: 99%
“…Surface patterning of β-CD was realized via PµCP with a PDMS stamp molded from a silicon wafer that was patterned through UV-lithography (150 µm broad line features and 50 µm broad spacing with 50 µm height, cut to about 0.75 cm 2 ; four plasma cycles of 1 min). 14,25 PµCP also generates a reactive surface for subsequent microchannel fabrication ( Fig. 1a(ii)).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reached sub-10 µm resolution by rotating the PDMS stamp during PµCP of a functionalized surface, which removes more of the surface functionalization. 14 In parallel, PDMS was poured into a 3D printed mold containing a ridge of size 20 × 2 × 0.5 mm (length × width × height), forming the PDMS replica after curing in the oven. This will form a microchannel over the glass surface with a volume of 20 µL.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that plasma etching, in combination with plasma microcontact patterning (PµCP), is a reproducible method for creating patterns of covalently bound molecules on glass surfaces. 14 In brief, a PDMS stamp, of the kind normally used for microcontact printing (µCP), is placed in contact with a covalently modified glass surface and the construct is subjected to plasma etching. Exposed molecules which are not protected by the PDMS stamp are decomposed by plasma, resulting in molecular patterns.…”
Section: Introductionmentioning
confidence: 99%
“…1a(i)): the glass functionalization with heptakis amino β-CD was carried out using 3-aminopropyltriethoxysilane (APTES) for obtaining an amine functionalized surface, 1,4phenylenediisothiocyanate (PDITC) for creating an amine reactive surface, and finally incubation of heptakis amino β-CD. Surface patterning of β-CD was realized via PµCP with a PDMS stamp (150 µm broad line features and 50 µm broad spacing with 50 µm height, cut to about 0.75 cm 2 ; four plasma cycles of 1 min), 14,23 also generating a reactive surface for subsequent microchannel fabrication ( Fig. 1a(ii)).…”
Section: Introductionmentioning
confidence: 99%